Improvement IL -10 and Reactive Oxygen Species (ROS) in HIV patients : Narrative Review - Franajayakk, Indra; Legiran; Salim, Eddy Mart; Hafy, Zen (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Background: Infection Human Immunodeficiency Virus (HIV) is still become problem scary health​ for world community . This virus infection causes a bunch symptom disease characterized by with weakening system immunity body . A collection of symptoms This known with designation Acquired Immune Deficiency Syndrome (AIDS). Consequence the decline system immunity , HIV sufferers will prone to For caught various disease infections that can have fatal consequences. Objective: For know How improvement IL-10 and Reactive Oxygen Species (ROS) levels in HIV patients . Research methods: This use Narrative Review design . Articles searched from Google Scholar, PubMed, Science Direct, and EMBASE/ Elviser with use relevant keywords , then chosen based on criteria that have been set , and objectives study . Results: Increased levels of IL-10 and Reactive Oxygen Species (ROS) in patients results in a decrease in the immune system, this is characterized by increased virus replication, deactivation macrophages and depletion of the number of lymphocytes, so that the progression of the infection towards AIDS can occur. Conclusion: HIV infection causes the occurrence dysfunction mitochondria and enhancement production Reactive Oxygen Species (ROS) in cells CD4 + T lymphocytes. Various viral proteins, such as the envelope proteins Gp120, Tat, Nef and Vpr , are able to increase ROS production through various different pathways. The increase in ROS that occurs can increase mRNA expression through activation Nuclear Factor Kappa B ( NFκB ), increased IL-10 mRNA expression ultimately will increase IL-10 levels